Pertuzumab, trastuzumab and taxane combination for visceral organ metastatic patients: Real life practice results - Esin, Ece; Çakmak Öksüzoğlu, Ömür Berna; Bilici, Ahmet; Çiçin, İrfan; Aksoy, Sercan; Alacacıoğlu, Ahmet; Kaplan, Mehmet Ali; Çabuk, Devrim; Sümbül, Ahmet Taner; Paydaş, Semra; Sakin, Ayşegül; Korkmaz, Tuba; et al. (Oxford University Press, 2018)
[Abstract Not Available]
Keywords: Taxane Combination; Metastatic Patients; Visceral Organ; Pertuzumab; Trastuzumab